2023
DOI: 10.1002/2211-5463.13539
|View full text |Cite
|
Sign up to set email alerts
|

Leptin accelerates BMSC transformation into vertebral epiphyseal plate chondrocytes by activating SENP1‐mediated deSUMOylation of SIRT3

Abstract: Bone marrow mesenchymal stem cells (BMSCs) are capable of multidirectional differentiation, and engrafted BMSCs can be used to replace damaged chondrocytes for treatment of intervertebral disc disease. However, chondroblast differentiation of implanted BMSCs is inhibited by the anoxic environment of the articular cavity. Here, we found that leptin enhanced the transformation of BMSCs into chondrocytes under hypoxic conditions. BMSCs isolated from mice were cultured in medium supplemented with leptin under hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…In addition, leptin levels were also increased by MAAM treatment in these mouse sera. Leptin, a hormone produced in adipocytes, plays a crucial role in maintaining a normal body weight and regulating energy expenditure (23)(24)(25). Our current data suggest that, in addition to the previously reported mitigative effects of GI-ARS in male Swiss mice, MAAM may also enhance the survival of male CD2F1 mice following radiation exposure by protecting against radiation-induced hematopoietic system failure.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, leptin levels were also increased by MAAM treatment in these mouse sera. Leptin, a hormone produced in adipocytes, plays a crucial role in maintaining a normal body weight and regulating energy expenditure (23)(24)(25). Our current data suggest that, in addition to the previously reported mitigative effects of GI-ARS in male Swiss mice, MAAM may also enhance the survival of male CD2F1 mice following radiation exposure by protecting against radiation-induced hematopoietic system failure.…”
Section: Discussionsupporting
confidence: 58%
“…47 According to Sun et al, IL-1β-mediated NADPH oxidase (Nox4) in chondrocyte metabolism might create excessive ROS, leading to matrix metalloproteinase-13 (MMP-13) release and articular cartilage breakdown. 48 Interestingly, treatment with RAR reversed the effects of IL-1β on the increase in ROS and decrease in SOD and GSH To investigate the mechanism of RAR in the treatment of OA, network pharmacology was performed. A total of 119 potential RAR-KOA targets were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Significant progress has been made in the treatment of IDD by MSCs, but due to the harsh environment of the IDs[ 5 ], the therapeutic effect of MSCs is reduced due to the lack of oxygen in the environment[ 61 ]. However, it has been found that the differentiation of MSCs to chondrocytes under hypoxic conditions can be helped by the addition of leptin[ 62 ], which provides energy for cell differentiation through its dependent glycolysis.…”
Section: Harsh Environment Of the Idmentioning
confidence: 99%